Pengaruh Employee Green Involvement, Green Training dan Green Image Terhadap Perception for Corporate Social Responsibility Perusahaan Pada PT Cabot Indonesia Jakarta - Raka Wardhani; Tiara Puspa (Universitas Medan Area, 2019)
The objective of this study is to examine and analyze the effect of brand logo identification, overall brand logo benefit toward customer loyalty through trust and commitment of Global System for Mobile (GSM) cellular operatorconsumers. The samples being used in this study is 200 respondents. The data collection method being used by this study is purposive sampling. The testing is conducted by using Structuctural Equation Model (SEM) analysis method. The findings of this study are: (1) endorser credibility identification has positive effect toward brand equity, (2) endorser credibility benefit has positive effect toward self-brand connection (3) self-brand connection has positive effect toward brand equity.